Treatment of Healthcare Waste – Myths and Truth in the 21st century - - Kühling, Jan-Gerd (International Journal of Infection Control, 2014)
While in the past hazardous healthcare waste was generally incinerated, if it was treated at all, in the last decade more comprehensive waste management systems have been set up and alternative treatment systems have emerged. The raising of awareness about healthcare waste issues and the application of advanced systems resulted however in an increase of uncertainties and mistaken ideas. An overview of the 7 most typical myths in modern healthcare waste treatment and the evidence-based truth on these myths are the subject of this paper. The myths to be discussed include the incineration of healthcare waste, the issue of waste “sterilization”, the myth of the need of shredding decontaminated waste, the disposal of blood, the usage of old and new autoclaves for the decontamination of waste and the centralized treatment of hazardous healthcare waste. The existing myths and related practical problems illustrate the great need of detailed, international technical standards and norms for healthcare waste treatment equipment. They also underline the need for standardized systems for the type testing of hazardous waste treatment systems and the need for standardized tests for installed treatment systems, as well as the need for clear protocols for the regular testing of waste treatment equipment.